2016
DOI: 10.1111/1754-9485.12484
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cutaneous squamous cell carcinoma of the head and neck with parotid metastases

Abstract: Despite multimodality treatment metastatic cHNSCC involving the parotid shows moderate rates of recurrence. Immunosuppressed patients with this disease have a particularly poor prognosis, demonstrating lower rates of CSS with similar rates of LRC compared to their immunocompetent counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
46
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 28 publications
8
46
2
3
Order By: Relevance
“…5,11,17 Given the increasing incidence of CSCC and the high morbidity and mortality of this disease, more data are needed to help guide adjuvant treatment recommendations to improve survival outcomes. 2,[7][8][9][10]18,19 Our In the present series, patients with tumors with PNI, increased diameter, poor differentiation, or regionally metastatic disease were more likely to undergo adjuvant therapy. Although these findings have been described as high-risk features for CSCC, only PNI and regional disease are currently recognized indications for adjuvant therapy.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…5,11,17 Given the increasing incidence of CSCC and the high morbidity and mortality of this disease, more data are needed to help guide adjuvant treatment recommendations to improve survival outcomes. 2,[7][8][9][10]18,19 Our In the present series, patients with tumors with PNI, increased diameter, poor differentiation, or regionally metastatic disease were more likely to undergo adjuvant therapy. Although these findings have been described as high-risk features for CSCC, only PNI and regional disease are currently recognized indications for adjuvant therapy.…”
Section: Discussionmentioning
confidence: 57%
“…3 In general, cure rates exceed 90% with early-stage disease [4][5][6] ; however, patients with locally advanced or regionally metastatic disease have higher rates of recurrence, with some reported 5-year overall survival (OS) estimates less than 50%. [7][8][9][10] Optimal treatment of advanced CSCC remains controversial because there are only a few large retrospective series that describe clinical outcomes, and no randomized clinical trials are available to guide decision making. Dermatologic series for all CSCCs have demonstrated that tumor differentiation, diameter, depth of invasion, and perineural invasion (PNI) are indicative of recurrence and poor survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Those are based mostly on single-institution reviews, as there are no national cancer registries that currently track the outcomes of cSCC. Risk factors for HNcSCC reportedly associated with worse outcomes include: advanced age, 6,7 size/diameter, 4,5,8,9 depth of invasion, 4,5,9 perineural invasion (PNI), 4,5,10,11 location, 5 poorly differentiated histology, 4,5,9,12,13 recurrent disease, 4 extranodal extension (ENE) of lymph nodes, 7,8,14,15 lymph node ratio, 6,16,17 immunosuppression, 6,11,[14][15][16][18][19][20] positive margins, 13,15,19,21 parotid metastases, 19,22 and disease-free interval. 23 Although many of these have been taken into consideration in the American Joint Committee on Cancer (AJCC) 8th Edition staging of HNcSCC, several others have been omitted.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with cutaneous squamous cell carcinoma (SCC) of the head and neck (cHNSCC) with metastases to the parotid gland or deep cervical lymph nodes are considered to be at moderate risk of locoregional failure and death. [1][2][3][4] Postoperative radiation therapy (PORT) is considered the standard of care in these patients because the available data suggests an improvement in locoregional control and survival. 5,6 In mucosal HNSCC (mHNSCC), prolongation of treatment package time (TPT -the interval between date of surgery and completion of PORT) beyond 11 to 14 weeks reduces both locoregional control and overall survival.…”
Section: Introductionmentioning
confidence: 99%